Assessment of nutritional status and health behaviors in yoga-trained women versus exercisers - Gogojewicz, Anna; Pilaczyńska-Szcześniak, Łucja; Popierz-Rydlewska, Natalia; León-Guereño, Patxi; Malchrowicz-Mośko, Ewa (Frontiers in Nutrition, 2024)
Introduction: Recreational physical activity is becoming more popular due to the increased public awareness about the beneficial effects on health status and quality of life. The aim of the study was to assess the nutritional status and health behaviors of women who regularly practice yoga as a form of physical recreation and to compare them with those who had not practiced before and had just signed up for yoga classes. A total of 143 women took part in this study. Methods: The nutritional status was assessed based on the obtained anthropometric measurements. The following indicators were calculated: Body Mass Index (BMI) and waist-to-hip ratio (WHR), determining the visceral accumulation of fat tissue. Health behaviors were assessed using a standardized five-point scale Health Behavior Inventory (HBI). Results: There were significant differences in the value of the general health behavior index, the sten scale, and the subscale regarding proper eating habits in the study groups compared to women who had not practiced yoga before (control group). Health behaviors indicators, particularly proper eating habits, are significantly higher in women participating regularly in yoga exercises, indicating a higher awareness among yoga practitioners.It can be suggested that yoga participation as a recreational physical activity can be an appropriate option for pursuing healthy habits.